Variation in Amino Acid Contents in the Different Cultivars of Rehmannia glutinosa Liboschitz - Kim, Haeng Hoon; Bong, Sun Ju; Kim, Hyun Ho; Han, Seung-Ho; Uddin, Md. Romij; Park, Sang Un (Asian Journal of Chemistry, 2015)
The present study investigated the composition of amino acids in different cultivars of Rehmannia glutinosa; 21 amino acids were detected in the nine cultivars investigated in this study. The level of amino acids varied markedly among the nine cultivars. The Wongang cultivar had the highest amount of amino acids (aspartic acid, glutamic acid, asparagine, serine, glutamine, histidine, phenylalanine, isoleucine and leucine), which was 4.64, 2.34, 1.93, 1.76, 1.73, 1.62, 1.29 and 1.22 times higher than that in Togang, Yeongang, Keumsanjaerae, Daegyung, Dagang, Jihwang1, Goryeo-jihwang and Gogang, respectively. The variation in the levels of glutamine, asparagine and leucine was considerably higher among the cultivars; the levels of glutamine and asparagine were 12.68 and 7.29 times higher, respectively, in Wongang cultivar than in Togang cultivar, which had the lowest content of amino acids. The levels of threonine, tyrosine, valine and methionine were the highest in the Goryeo-jihwang cultivar. The content of g-aminobutyric acid was considerably higher in Keumsanjaerae and was 7.43, 2.75, 3.52, 3.48, 4.06, 1.69, 5.26 and 4.35 times higher than that in Yeongang, Gogang, Dagang, Daegyung, Goryeo-jihwang, Wongang, Jihwang1 and Togang, respectively. The levels of argentine, tryptophan and lysine were the highest in Gogang cultivar. The level of glycine was 1.83 times higher in Yeongang cultivar than that in Daegyung cultivar. Present results suggested that R. glutinosa cultivars contain varying amounts of amino acids and the Wongang cultivar might have an excellent potential to be used as a source of amino acids.